Changes of Southern Hemisphere westerlies in the future warming climate - Deng, Kaiqiang; Azorin-Molina, Cesar; Yang, Song; Hu, Chundi; Zhang, Gangfeng; Minola, Lorenzo; Chen, Deliang (Atmospheric research, 2022)
The Southern Hemisphere westerlies (SHWs) play a key role in regulating global climate and ocean circulation, but their future changes under low to high greenhouse gas forcings remain unclear. This study investigates the long-term trends in strength and position of the SHWs and their linkage with human activities, based on the ERA5 reanalysis and model simulations from the Coupled Model Intercomparison Project phase 6 (CMIP6). The results show that the SHWs have intensified and shifted poleward in the recent decades, and are projected to experience divergent trends in strength and position during the 21st century under different Shared Socioeconomic Pathway (SSP) scenarios. Forced by SSP245, 370, and 585, which represent the middle to high greenhouse gas forcings, the SHWs will continue to strengthen and move southward in 2015–2099, with the largest trends induced by SSP585. Nevertheless, forced by SSP126, which implies a low greenhouse gas forcing in the future, the ongoing trends in strength and position of the SHWs will be interrupted and even reversed. Further investigation reveals that the anthropogenic forcing could have affected and will likely influence the SHWs by modulating meridional atmospheric circulation in the Southern Hemisphere. In particular, the Southern Annular Mode and the tropical Pacific convection play crucial roles in the changes of SHWs. This study links human activities to the changes in SHWs, providing important implications for climate change and its mitigation. •The Southern Hemisphere westerlies (SHWs) have strengthened and shifted poleward in the recent decades.•The SHWs are projected to intensify (weaken) during the 21st century under high (low) greenhouse gas forcing.•Human activities may play a key role in the changes of SHWs.